First record of the planthopper tribe Adenissini (Hemiptera: Caliscelidae) from Socotra Island, with description of a new genus and two new species - Gnezdilov, Vladimir M.; Malenovský, Igor (European Journal of Taxonomy, 2023)
The planthopper family Caliscelidae (Hemiptera: Auchenorrhyncha: Fulgoromorpha) and the tribe Adenissini are recorded here for the first time from the Socotra Archipelago (Yemen). A new genus, Oceatra gen. nov., is described for two new species from Socotra Island – Oceatra litoralis gen. et sp. nov. (type species) from coastal sand dunes and salt marshes, and O. scandens gen. et sp. nov. from evergreen montane woodland and shrub communities of the Hagher mountains. Oceatra gen. nov. is similar to Perissana Metcalf, 1952 but differs in the structure of the male style and phallobase. A key to distinguish the genera of the subtribe Adenissina is provided.